Research on Construction Quality Control of Expansion joint in Road and Bridge Engineering - Du, Xiangwen (Journal of Theory and Practice of Management Science, 2023)
The construction technology of Expansion joint is a key link in the construction of highway bridges, which has a great impact on the overall quality of the bridge, so it is very important to strengthen the control of its construction technology. In the future construction of Expansion joint of highway bridges, attention should be paid to the construction operation and the management of construction personnel, so as to effectively ensure the safety of highway traffic and extend the service life of the highway.